Meta Analysis: Effect of Inadequate Gestational Weight Gain on Low Birth Weight and Small for Gestational Age - Amrika Putranti, Maurizka Pitria; Murti, Bhisma; Adriani, Rita Benya (Journal of Maternal and Child Health, 2023)
Background: Weight gain during pregnancy is related to optimizing health for both mother and baby. In addition, the increase in pregnancy weight is also an important indicator of maternal nutrition fulfillment during pregnancy and is a good measure to monitor fetal growth. This study aims to estimate the average effect of inadequate gestational weight gain on the risk of low birth weight and small for gestational age. Subjects and Method: This was a systematic review and meta-analysis with PRISMA guideline and PICO model. Population: pregnant women. Intervention: inadequate gestational weight gain. Comparison: normal gestational weight gain. Outcome: low birth weight and small for gestational age.  Online databases used are PubMed, SpringerLink, Scopus, and ProQuest with the keywords "Gestational Weight Gain" OR “Inadequate Weight Gain" AND "Low Birth Weight" OR "Birth Weight Infant” OR “Pregnancy Outcomes" AND "Small Gestational Age" AND "Multivariate" AND "Cohort". There were 19 cohort studies published in 2013-2022 that met the inclusion criteria. The analysis was conducted using the Review Manager 5.3 application. Results: Meta-analysis using 19 cohort studies showed that pregnant women with inadequate weight gain had a risk of giving birth to infants with low birth weight 1.94 times compared to those with normal gestational weight (aOR= 1.94; CI 95%=1.74 to 2.16; p<0.001) and pregnant women with inadequate gestational weight gain had 1.69 times higher risk of giving birth to infants with small for gestational age than those with normal gestational weight (aOR= 1.69; 95% CI= 1.55 to 1.85; p<0.001). Conclusion: Inadequate gestational weight gain increases the risk of low birth weight and small for gestational age. Keywords: Pregnant women, gestational weight gain, low birth weight, small for gestational age Correspondence: Maurizka Pitria Amrika Putranti. Master's Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: maurizka27@gmail.com. Mobile: +6285290846373